MEMPERKUAT DAKWAH TRANSFORMATIF SEBAGAI SALAH SATU LANGKAH UNTUK MEMBANGUN IDENTITAS BANGSA YANG BERKEADABAN - Nelmaya Nelmaya (Islam Transformatif : Journal of Islamic Studies, 2019)
Indonesia is one of the largest Muslim populations in the world, with a total of 182,083,594 Muslims out of a total population of 224 million. As the largest population, Muslims have an essential role in building a civilized Indonesian identity. The problem now is, the civilized nation's identity has not been realized as expected, this can be seen from a variety of indicators, including indicators of Indonesian poverty still believing at least 37.17 million people are poor, crime is again ballooning, harmonization has not materialized because everywhere happens conflicts, including religious conflicts, Indonesia's achievements, and well-being are still far compared to other countries and so on. However, from the various indicators put forward, one thing which is superficial to form as a builder of civilization in Indonesia is social capital. The social capital of this nation is still ripped apart because it is not built with clear mass communication and has a paradigm that can dialogue textuality and contextuality. In this connection, Islam has a tradition of da'wah and is still developing today. This da'wah tradition is a potential asset that can build social capital to improve the nation's identity, which is still within the framework of this massive and anomie civilization. For da'wah to be used as a basis in this direction, da'wah must also develop normative methods and strategies that are appropriate to the present context. This paper offers transformative da'wah as a builder of social capital to realize a civilized nation's identity.